Factors Affecting the Occurrence of Mental Disability in Ponorogo District, East Java - Purwiyanti, Risye Endri; Soemanto, RB.; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2017)
Background: Children with mental disability show below average intellectual abilities and social behavior adaptability. Living with a disabled child can have profound effects on the entire familyÃ¢â¬âparents, siblings, and extended family members. Meeting the needs of children with disabilities can be challenging for schools and families. However, effective support for childrenÃ¢â¬â¢s mental health and wellbeing involves efforts to meet the social, emotional and learning needs of all children. This study aimed to investigate factors affecting the occurrence of mental disability in children aged 6 to 15 years old.Subjects and Method: This was an analytic observational study using case control design. The study was conducted in Ponorogo District, East Java, from March to April 2017. A sample of 150 children aged 6 to 15 years old, consisting of 50 children with mental disability and 100 children without mental disability, were selected for this study by fixed disease sampling. The exogenous variables were prematurity, maternal age during pregnancy, maternal stress during pregnancy, hereditary history, family income, parental education, and environmental exposure. The endogenous variables were maternal nutritional status, low birthweight, and mental disability. The data were collected by a questionnaire, and analyzed by path analysis.Results: Mental disability was directly affected by maternal age (b= 2.52, 95% CI = 1.23 to 3.81, p<0.001), low birthweight (b= 2.32, 95% CI = 1.11 to 3.54, p<0.001), hereditary history (b= 2.54, 95% CI = 1.34 to 3.74, p<0.001). Mental disability was indirectly affected by maternal nutritional status, maternal stress, maternal education, family income, and environmental exposure.Conclusion: Maternal age, low birthweight, and hereditary history, directly affect mental disability. Maternal nutritional status, maternal stress, maternal education, family income, and environmental exposure, indirectly affect mental disability.Keywords: mental disability, children aged 6 to 15 years oldCorrespondence:ÃÂ Risye Endri Purwiyanti. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java, Indonesia. Email: risye310390@gmail.com. Mobile: 085736575029.Journal of Maternal and Child Health (2017), 2(3): 257-269https://doi.org/10.26911/thejmch.2017.02.03.07